PNIPAM-based extracellular K+ fluorescent sensor for high-throughput analysis. (December 2021) - Shen, Min; Pan, Tingting; Ning, Juewei; Shi, Jiayan; Liu, Hongtian; Tian, Yanqing
Abstract: We report on the fabrication of K + fluorescent sensor P2 based on thermoresponsive poly(N-isopropylacrylamide) and small molecule K + fluorescent sensor KS. P2 changed its size with a range from 35 °C to 42 °C and exhibited lower critical solution temperature (LCST) at 38 °C. The LCST affected the polymer's nanostructures and microenvironment of KS, which in turn affected P2 's fluorescence intensities and responses to K + . Furthermore, P2 exhibited high selectivity and sensitivity to K + with a dynamic response range from 1 to 20 mM, enabling its suitableness for extracellular K + analysis. The sensor was further used to in situ monitor the K + fluctuation of Escherichia coli and B. Subtilis 168 bacteria under lysozyme stimulation in 96 well plate by a high throughput analysis approach, and cell species dependent K + release was observed. The PNIPAM-based K + sensor P2 shows potential application in antimicrobial drugs/peptides screening. Highlights: The new polymeric K + fluorescent sensor P2 exhibited superior sensitivity, selectivity and solubility in water. The higher fluorescence intensities at 37 °C made P2 more advantageous in biological applications. P2 can be used to in situ monitor the K + fluctuation of bacteria under lysozyme stimulation by a high throughput method.